Expanding Pathobiological Mechanisms in Hypertrophic Cardiomyopathy to Explain Heterogeneity: JACC Review Topic of the Week - Maron, Barry J. (J Am Coll Cardiol, 2019)
Hypertrophic cardiomyopathy (HCM) has been considered a heterogeneous cardiac disease ascribed solely to single sarcomere gene mutations. Limitations of this hypothesis suggest that sarcomere mutations alone do not adequately explain all HCM clinical and pathobiologic features. Disease-causing sarcomere mutations are absent in ~70% of patients with established disease, and sarcomere gene carriers can live to advanced ages without developing HCM. Some features of HCM are also inconsistent with the single sarcomere gene hypothesis, such as regional left ventricular (LV) hypertrophy and myocardial fibrosis, as well as structurally abnormal elongated mitral valve leaflets and remodeled intramural coronary arterioles, which involve tissue types that do not express cardiomyocyte sarcomere proteins. It is timely to expand the HCM research focus beyond a single molecular event toward more inclusive models to explain this disease in its entirety. We chart paths forward addressing this knowledge gap utilizing novel analytical approaches, particularly network medicine, to unravel the pathobiologic complexity of HCM.